1993
DOI: 10.1007/bf01379088
|View full text |Cite
|
Sign up to set email alerts
|

Electropherotypes, serotypes, and subgroups of equine rotaviruses isolated in Japan

Abstract: Electropherotypes (ET), serotypes, and subgroups of equine rotaviruses isolated from foals in Japan were determined. The ETs of 136 isolates from 1981 through to 1991 were divided into six groups: ET-A-ET-F. The ET-A, -B, -C, -D, -E, and -F were present in 3, 1, 121, 9, 1, and 1 strains, respectively. Representative viruses of ET-A, -B, -C, and -D were identified as serotype G3. Viruses of ET-E and -F were identified as serotypes G 10 and G 5, respectively. The four representative viruses of serotype G 3 did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Almost all of the Irish strains (98%) possessed a P [12] VP4 genotype. This P type appears to be predominant in equine GARVs (5,16,32), although other P types have also been identified sporadically, such as P [1], P [7], and P [18] (9,27,28,32,33).…”
Section: Discussionmentioning
confidence: 97%
“…Almost all of the Irish strains (98%) possessed a P [12] VP4 genotype. This P type appears to be predominant in equine GARVs (5,16,32), although other P types have also been identified sporadically, such as P [1], P [7], and P [18] (9,27,28,32,33).…”
Section: Discussionmentioning
confidence: 97%
“…Equine rotavirus HO-5 strain (G3P [12]) [7,10] was used as the vaccine strain. Culture fluids of the virus (10 7.3 TCID 50 /2 ml) were propagated on a monolayer of MA-104 cells by the methods described in a previous report [5].…”
Section: Vaccinementioning
confidence: 99%
“…The serotypes and genotypes of rotaviruses are classified by differences in the antigenicity of two kinds of viral outer capsid protein (VP4 and VP7) or the VP4 coding gene. It has been confirmed that both the G3P [12] and G14P [12] rotaviruses spread in the Hidaka region of Hokkaido in 1996 and 1997 [14], although the G3P [12] rotavirus emerged between 1981 and 1991 [7,11,13]. It has been suggested that the G3P [12] rotavirus was predominant in surveys conducted on sera collected from yearlings in the same region in 1999, but the G14P [ 1 2 ] r o t a v i r u s h a s a l s o s p r e a d [ 8 ] .…”
mentioning
confidence: 99%
“…A reverse transcriptase PCR assay (64) and an enzyme-linked immunosorbent assay (ELISA) (7) have been developed for G typing, and hybridization assays with specific probes have been used in P typing of equine group A rotaviruses (35,39). Strains belonging to the G3,P4 [12] serotype are most prevalent in diarrheic foals, followed by those belonging to the G14,P4 [12] serotype (4,5,7,13,28,33,36,37,39,50,64). Single isolates, each belonging to G5,P9 [7] (H-1) (12,28,32), G8,P6 [1] (Eq/26/94) (39), G10,P8 [11] (Eq/R-22) (35), and G13,P [18] (L338) (6) genotypes/serotypes, have been reported for young horses suffering from diarrhea.…”
mentioning
confidence: 99%